The role of MAPK pathway in gastric cancer: unveiling molecular crosstalk and therapeutic prospects - Yuan, Weiwei; Shi, Yin; Dai, Shiping; Deng, Mao; Zhu, Kai; Xu, Yuanmin; Chen, Zhangming; Xu, Zhou; Zhang, Tianlong; Liang, Song (Journal of translational medicine, 2024)
Gastric cancer remains a significant health burden globally, especially prevalent in Asian and European regions. Despite a notable decline in incidence in the United States and Western Europe over recent decades, the disease's persistence underscores the urgency for advanced research in its pathogenesis and treatment strategies. Central to this pursuit is the exploration of the mitogen-activated protein kinase (MAPK) pathway, a pivotal cellular mechanism implicated in the complex processes of gastric cancer development, including cellular proliferation, invasion, migration, and metastasis. The MAPK or extracellular signal-regulated kinase pathway serves as a crucial conduit for transmitting extracellular signals to elicit intracellular responses, with its signaling cascades subject to alterations due to genetic and epigenetic variations across various diseases, prominently cancer. This review delves into the intricate role of the MAPK signaling pathway in the pathogenesis of gastric cancer, drawing upon the most recent and critical studies that shed light on MAPK pathway alterations as a gateway to the disease. It highlights the pathway's involvement in Helicobacter pylori-mediated gastric carcinogenesis and the tumorigenic processes induced by the Epstein-Barr virus, showcasing the substantial influence of miRNAs and lncRNAs in modulating gastric cancer's biological properties through their interaction with the MAPK pathway. Furthermore, the review extends into the therapeutic arena, discussing the promising impacts of herbal medicines, MAPK pathway inhibitors, and immunosuppressants on mitigating gastric cancer's progression. Through an exhaustive examination of the MAPK pathway's multifaceted role in gastric cancer, from molecular crosstalks to therapeutic prospects, this review aspires to contribute to the ongoing efforts in understanding and combating this global health challenge, paving the way for novel therapeutic interventions and improved patient outcomes.